Fleeing justice, chasing escapers: preliminary observations on prison escape in the Ius commune: Peer reviewed article (Italian Review of Legal History, 2021)
The origin of prison punishment has recently been subjected to renewed scrutiny: on one hand, Michel Foucault and the historiography which followed his teachings asserted that the only proper way of visualizing the historical origin of prison punishment is to point to the Enligthment Age, in which the right economic and cultural conditions were sufficiently present to allow its springing; on the other, Guy Geltner has convincingly demonstrated, through documentary and archival sources, that 13th century Italy knew not only various forms of prison punishment but also that the local municipal administrations managed to establish authentic (if elementary) forms of prison’s organization.In regarding the phenomenon of prison escape, the first historiography, coherently, did not take into account any form of Medieval or Early Modern jail breaking (even if the escapes were famous and well known as the one of Hugo Grotius, which the paper recounts in the first paragraph); the second historiography contemplated the possibility of mates breaching bonds and taking their chance to conquer freedom but concluded that this was a rare occurrence. Neither of these historiographies, after all, analysed what the law prescribed on this subject.This paper aims to fill this gap: the second paragraph is thus devoted first to illustrate the content of some Roman law’s prescription on the subject, where the most probable punishment for the prisoners who committed jail breaking was of capital sort (which in Roman law didn’t mean necessarily death but inevitably involved some loss of liberty, properties or – in the gravest case – life or limb).Then, it proceeds to expound the different interpretations that the 14th century’s jurists produced on the topic: beginning from the only known treaty ever written in the Middle Age on the subject of prison and walking throughout the various readings offered on the subject by law professors, attorneys and judges, the paper shows that, albeit capital punishment still persisted during the course of the entire century, the teachings of the jurists tried to distinguish between prison escapes that deserved death (such as was the case when the prisoners harmed the guards in order to obtain their freedom), prison escapes that made the fugitive fictitiously confess (being the technique used here by lawyers a true fictio iuris) the crime for which they were in the first place incarcerated and prison escapes that were punished by judges using their vast arsenal of arbitrary powers (power that, when used properly, did not extend, ever, to death). Things, the paper continues to show, were not so much different in Church’s court, where the repression of heresy demanded the direct intervention of the Pope: the subsequent reading of the orders produce by the papacy by canonists confirms that provisions similar to the ones adopted into secular courts were also well known in ecclesiastical ones. It was not until the beginning of the Early Modern Age that some light began to shine over this bleak picture: through the systematization of the criminal law conducted by the first manuals (practicae), which specifically addressed this not yet independent branch of thelegal order, the crime of prison escape was placed into a more homogeneous perspective.Usually written by jurists who daily practiced law in courts as judges or lawyers, these texts report the certainly not desirable (and sometimes inhumane) conditions in which mates were confined but also about the evolution through which the crime of prisonescape was inexorably attracted into the orbit of judicial discretion (arbitrium) and, ultimately, far away from the death penalty which Roman law originally fulminated. The last part of the central paragraph is then devoted to the exam of some consilia (allegations written by lawyers on behalf of clients who attempted or managed to escape or by consultants called to advise the court) and decisiones (decisions adopted by supreme sovereign courts), which contribute to add more details to the analysis and to confirm the impression that the punishment for jail breaking was, at least in the Early Modern Age, not any more considered to be worth of capital punishment.The last considerations of the entire essay are, finally, inspired by the pages of the Dutch law professor Anton Mattheus II (1601-1654), who thoroughly confirm the evolution trend in the punishing of jail breaking and cite the very case of the prison escape of his countrymen Hugo Grotius, with which the essay begins.
Keywords: Prison Escape; Criminal Legal History; Utrumque ius; Hugo Grotius; Cultural Legal History